Examination Of Problematic Internet Use In Information Technology Department Students In Terms Of Different Variables (Malatya Sample) - Bahçeci, Ferhat (My University, 2019)
The main aim of this study is to describe the level of problematic internet use forstudents in Malatya who study in the field of information technology in thevocational secondary education institutions. In this study, general screeningmethod was used. Online Cognition Scale (OCS) and the questionnaire involvingdemographic information form were used as data collection tools. The universe ofthe study consists of all information technology students (N = 482) at thevocational and secondary level in Malatya. As data analysis tool, 36-item OnlineCognition Scale with seven-point Likert scale and demographic form developedby researchers were used. Cronbach's alpha (a) internal consistency coefficient ofthe scale was found to be 0.91. In this study, 312 volunteer students selected inthe universe were surveyed and the data of 310 individuals who were understoodto fill the questionnaire correctly were included in the analysis. Of the 310individuals involved in the survey, 131 (42.2%) were found to be problematicinternet users. This rate shows that a significant number of students who make upthe working group are problematic internet users. One-way ANOVA and t-testwere performed separately to data of all groups and the data obtained from theproblematic internet user group. Whether use of the internet is affected bydifferent variables such as gender, age, registering to social network, attitudestowards occupational fields, and having internet at home or not was investigatedaccording to data obtained. As a result of analyses, it was determined that whilethere was no relationship between daily internet usage time and problematicinternet use, there was a significant relationship between both groups in terms ofsocial network and problematic internet use. It was concluded that gender did nothave any contribution to problematic internet use.
Keywords: Eğitim; Eğitim Araştırmaları